2023
DOI: 10.1002/adma.202306583
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Biomimetic Nanovesicles in Brain Diseases

Qing You,
Fuming Liang,
Gege Wu
et al.

Abstract: Brain diseases, such as brain tumors, neurodegenerative diseases, cerebrovascular diseases and brain injuries, are caused by various pathophysiological changes such as excessive or impaired angiogenesis, neuroinflammation, immune activation or suppression, neurodegenerative disorders, and neurovirulent protein deposition, which poses a serious health threat. Brain disorders are often difficult to treat due to the presence of the blood‐brain barrier (BBB), which hinders the delivery of drugs to the brain. Biomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 270 publications
0
5
0
Order By: Relevance
“…An alternative emerging strategy could be represented by the exploitation of one particular route of communication utilized by many cell populations not only in the CNS, i.e., the release of extracellular vesicles (EVs). EVs are classified based on their dimensions, are delimited by a double layer membrane, contain a huge variety of cell components, including nucleic acids, proteins, small interfering RNAs, neurotransmitters, lipids and others [102], and are produced under physiological conditions by virtually all cells in the body to promote cell-to-cell communication. Since they are often released in the bloodstream and in other circulating fluids, including the cerebrospinal fluid, their effects can be observed at a distance from the cell of origin.…”
Section: Glial Cells As Drugs Themselves: Administration Of Glia-deri...mentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative emerging strategy could be represented by the exploitation of one particular route of communication utilized by many cell populations not only in the CNS, i.e., the release of extracellular vesicles (EVs). EVs are classified based on their dimensions, are delimited by a double layer membrane, contain a huge variety of cell components, including nucleic acids, proteins, small interfering RNAs, neurotransmitters, lipids and others [102], and are produced under physiological conditions by virtually all cells in the body to promote cell-to-cell communication. Since they are often released in the bloodstream and in other circulating fluids, including the cerebrospinal fluid, their effects can be observed at a distance from the cell of origin.…”
Section: Glial Cells As Drugs Themselves: Administration Of Glia-deri...mentioning
confidence: 99%
“…Alternative strategies, including the laboratory production of artificial nanovesicles, are currently under development, so that their composition, structure and characteristics can be fully controlled and modulated according to the needs of a specific patient. Not less importantly, thanks to their ability to permeate the blood-brain barrier, EVs can also be utilized to directly deliver drugs to the CNS, as recently reviewed in [102].…”
Section: Glial Cells As Drugs Themselves: Administration Of Glia-deri...mentioning
confidence: 99%
“…Considering the inevitability of the formation and its criticality to the fate of NPs, the exploration of PCs may provide an insight for NPs to overcome the BB in GIT. 17,19 Artificial biomimetic coatings (e.g., cell membrane coated particles, 25,26 reconstructed extracellular vesicles 27,28 ) could greatly improve the drug delivery efficiency of NDDS via influencing the nanobio interaction. 26,29 Recent research has demonstrated that the negative impacts of PCs can be surmounted and converted to beneficial impacts based on the artificial reconstruction of PCs coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial biomimetic coatings (e.g., cell membrane coated particles, , reconstructed extracellular vesicles , ) could greatly improve the drug delivery efficiency of NDDS via influencing the nanobio interaction. , Recent research has demonstrated that the negative impacts of PCs can be surmounted and converted to beneficial impacts based on the artificial reconstruction of PCs coatings. ,, For example, Liu et al found that the key to slowing the clearance of viral vaccines (OVs) from the bloodstream was to restrict the natural formation of viral-PCs in the plasma. Therefore, they used serum proteins to form artificial virus-PCs on OVs, which prevented the formation of viral-PCs and reduced clearance rates.…”
Section: Introductionmentioning
confidence: 99%
“…It is helping to reduce their limitations and maximize their advantages. Moreover, in the aspect of the outer shell, the biomembranes can be extracted from various sources, including red blood cells, glioma cells, brain metastatic tumor cells, immune cells, exosomes and so on [12] . The coating of different biomembranes can endow nanocomposites with different capabilities, such as good biocompatibility, extended circulation time, homologous tumor or inflammation targeting, and enhanced BBB penetration, facilitating efficient monitoring of disease progression, accurate differentiation of tumor tissues, and significant improvement of anti‐tumor effectiveness [13] …”
Section: Introductionmentioning
confidence: 99%